Bioactive materials in dentistry: Remineralization and biomineralization - Benetti, Francine [UNESP] (My University, 2019)
Bioactive materials, or biomaterials, have the ability to interact biologically with the tissue to which it is inserted, and to stimulate the deposition of mineralized tissue. The calcium phosphate-based ceramics were the first known materials in dentistry to have bioactivity, and currently, these materials are the most used for biomedical purposes, with different morphological characteristics. In dentistry, these materials have achieved immense importance by stimulating the deposition of osseous tissue in injured bone, and by having the ability to remineralize hard tooth tissues (enamel and dentin). Furthermore, repair materials based on aggregated trioxides mineral or on calcium hydroxide are classic biomaterials and widely used in dentistry, mainly in contact with the pulp tissue or periodontal ligament, for repair processes. However, various formulations of these materials appear all the time, in search of the ideal material. In general, bioactive materials have been shown to promote the release of calcium, sodium, silicon and phosphate ions, which are metabolized by the body, having effects such as angiogenesis and antimicrobial action, which can be improved depending on the composition of the material. Pulp tissue is a highly specialized dental tissue and is the subject of intense studies about the response to biomaterials. It is also understood that some systemic alterations in individuals have an influence on the action of bioactive materials during tissue repair processes. Thus, this book will address the use of different bioactive materials in dentistry, considering the performance of these biomaterials in the hard tissues of the tooth, and the response of the dental pulp, as well as the influence of the composition of these materials and of the individual's systemic alterations in bioactivity and in antimicrobial activity. The several in vivo and in vitro tests to evaluate the bioactivity of a biomaterial will also be addressed.